Improvement of the System of Assessment and Management of Financial Security of State Joint-Stock Companies (The Peerian Journal, 2023)
In this article, as a result of economic reforms and privatization of state property, sole ownership was abolished and new forms of ownership began to develop, in particular, joint-stock companies. At the same time, creating favorable conditions and legal basis for the development of private enterprises, limited liability companies and other organizational and legal structures